PENGARUH LATIHAN RELAY DRIBBLE DENGAN CEPAT TERHADAP KECEPATAN DRIBBLE PADA EKSTRAKURIKULER SEPAKBOLA SMK KEHUTANAN PEKANBARU - Dwi Saputro; Ramadi '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Base on field observations conducted by researchers, that there are some problem or phenomena that occur in the game extracurricurel football SMK Kehutanan Pekanbaru, namely the lack of mastering technique of playing the ball. such as dribble ie the ball is often dribbled away from the foot of the player, ball contol is not good when dribbing, so players often lose the ball while dribbling. the purpose of this study research was the determine the effect of effect on Dribble Speed to Quikly Relay Dribble and Driblle Speed Football Extracurriculer Smk Kehutanan Pekanbru. The population in this study research were as many as 14 people. insrumen used in this research in the dribble. Data were analyzed using test. based uji- t produce tcount of 3,40 to 1,761 ttabel then H_a received. on the level of alpha (α) 0,05. it can be concluded that there is significant influence offect on dribble speed to quikly relay dribble and dribble speed football extracurriculer SMK kehutanan pekanbaruKeywords: Relay Dribble Quikly, Dribble Speed